The Influence Of Servicescape On Customer Satisfaction Mediated By Brand Image (Study Of Mie Gacoan Consumer In Denpasar City) - Kadek Hery Krista Yana; Gede Suparna (PT Publikasiku Academic Solution, 2024)
The success of a business does not escape the attention of customer satisfaction factors. Customer dissatisfaction with a product will usually lead to complaints. One of the companies that received these complaints was Mie Gacoan in Denpasar City. Based on a total of 100 assessments of Mie Gacoan in Denpasar City, it can be seen that the majority of consumers gave one star. The meaning of giving one star is that consumers feel that the environment provided is very bad, two stars are not good, three stars are quite good, four stars are good, and five stars are very good. There are factors that need to be considered in overcoming customer dissatisfaction, one of which is servicescape. This research aims to explain the influence of servicescape on customer satisfaction which is mediated by brand image. The number of samples taken was 130 respondents, with a non-probability sampling technique and the method used was purposive sampling. The data collection method is a survey by distributing questionnaires. The analysis technique used is path analysis using the SPSS program. The research results show that servicescape has a positive and significant effect on customer satisfaction. These results show that a good and quality servicescape can increase the satisfaction felt by customers. Brand image also has a positive and significant effect on customer satisfaction, which means that the stronger the brand image, the higher the customer satisfaction. Brand image is also able to partially mediate the effect of servicescape on customer satisfaction.